2021
DOI: 10.1038/s41598-021-83351-5
|View full text |Cite
|
Sign up to set email alerts
|

A summary of eye-related visits to a tertiary emergency department

Abstract: Timely ophthalmologic consultation is important to ensure patients receive high quality ophthalmologic care in the Emergency Department (ED). Tele-ophthalmology may prove useful in safely and efficiently managing ED eye-related complaints. Prior to implementing such a solution, current consultation patterns must be understood. We aimed to assess case-mix acuity and consultation workflow patterns in the ophthalmology consult service at a tertiary emergency department in New York City. The medical records of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[9,15,16] This nding is similar to previous literature which has demonstrated that between 44% and 60% of ophthalmic presentations to the ED were for nonemergent problems. [14,17] In this investigation, 87% of patients reported having access to a primary care provider; systems level changes to help redirect patients with nonurgent presentations to more appropriate care can help with ED overcrowding. [18,19] The results of this investigation are of particular importance given the increase in burnout seen by ED providers from the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[9,15,16] This nding is similar to previous literature which has demonstrated that between 44% and 60% of ophthalmic presentations to the ED were for nonemergent problems. [14,17] In this investigation, 87% of patients reported having access to a primary care provider; systems level changes to help redirect patients with nonurgent presentations to more appropriate care can help with ED overcrowding. [18,19] The results of this investigation are of particular importance given the increase in burnout seen by ED providers from the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…These results are in-keeping with previous investigations which have similarly demonstrated anterior segment pathology to be most frequent impetus for patient presentation to the ED. [17,22,23] As such, approaches to frequent corneal and external eye conditions should be a signi cant focus of emergency medicine teaching. Recognizing emergent vision threatening presentations and when to consult ophthalmology should instead be the focus for presentations that are less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal abrasions and foreign bodies on the ocular surface are two of the most common ophthalmic complaints of patients presenting to the emergency departments [ 1 ]. Some ocular complaints, although not emergent, can cause extreme discomfort to the patient, whereas other problems can be vision threatening and require immediate ophthalmological consultation [ 2 ]. The cornea is richly innervated, hence corneal foreign bodies can present with symptoms like pain.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients visiting EDs with ophthalmic primary complaints, corneal abrasions and foreign bodies (FBs) on the ocular surface are among the leading diagnoses, and these two diagnoses respectively represent approximately 13–14% and 8–15% of the complaints 4 , 5 . These patients probably visited the ED because of persistent ocular FB sensation and concerns that a FB remained inside the eye.…”
Section: Introductionmentioning
confidence: 99%
“…These patients probably visited the ED because of persistent ocular FB sensation and concerns that a FB remained inside the eye. However, a recent report from New York City revealed that the time from triage to completion of an ophthalmologic consultation for patients complaining of FB sensation was long: 174–263 min 5 .…”
Section: Introductionmentioning
confidence: 99%